2015
DOI: 10.4046/trd.2015.78.4.419
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Course of Endobronchial Inflammatory Polyps as a Complication after Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration

Abstract: We presented a case of unusual endobronchial inflammatory polyps as a complication following endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in a patient with tuberculous lymphadenitis. EBUS-TBNA of the right hilar lymph node was performed in a 29-year-old, previously healthy man. The patient was confirmed with tuberculous lymphadenitis and received antituberculosis medication over the course of 6 months. Chest computed tomography, after 6 months of antituberculosis therapy followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Most cases had single lesion, while in two patients, multiple TPNR were present. [ 6 9 ] TPNR resolved spontaneously or with conservative medical management in three of the six patients. Bronchoscopic interventions were performed in three of the six patients (50%) that included rigid bronchoscopy with argon plasma coagulation (APC), cryotherapy, and flexible bronchoscopic biopsy-assisted removal.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Most cases had single lesion, while in two patients, multiple TPNR were present. [ 6 9 ] TPNR resolved spontaneously or with conservative medical management in three of the six patients. Bronchoscopic interventions were performed in three of the six patients (50%) that included rigid bronchoscopy with argon plasma coagulation (APC), cryotherapy, and flexible bronchoscopic biopsy-assisted removal.…”
Section: Discussionmentioning
confidence: 92%
“…Our systematic review of the literature identified five studies (all case reports) describing six patients wherein a TPNR occurred following EBUS-TBNA. [ 5 6 7 8 9 ] The clinical diagnosis was suspected malignancy in four patients and TB in two patients. A 22-gauge EBUS-TBNA needle was used in three patients whereas the needle gauge was not reported in three patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bronchial polyps are developed by epithelialization secondary to bronchial mucosa injury with submucosal extension, such as intubation or thermal injury, and damage to the fibrous connective tissue with the infiltration of inflammatory cells (5,8,9). Although pathological findings could not be evaluated in the current case, a classical inflammatory bronchial polyp is the most likely diagnosis because of its appearance and clinical course (10). However, it remains a matter of speculation.…”
Section: A B C Dmentioning
confidence: 87%
“…The natural course of inflammatory bronchial polyps remains unknown because the majority of them are removed for symptomatic relief (10). Meanwhile, in a case following endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) reported by Lee et al, the inflammatory bronchial polyp regressed spontaneously without treatment (10).…”
Section: A B C Dmentioning
confidence: 99%